Optimization of autonomous inflow control device performance through evaluation study on pressure distribution on levitating disc: article - Baharin, Muhammad Aiman; Md Yusof, Nadiahnor (2018)
Oil and gas industry is facing critical challenge in maintaining production performance. High water production due to strong aquifer and water injection decrease the performance of a well. Implementation of Autonomous Inflow Control Device inside a completion system shall help improve the total performance of a well. The device work autonomously where a levitating disc control the inflow based on the composition and velocity of the fluid produced. Each field require specific design of the device to be implemented. The purpose of this paper is to determine the optimum flow area for the device to work effectively in a well condition specified. This will verify the effects of a few design parameter of the device focused such as inlet area, disc size and outlet size. Simulations using ANSYS Fluent were done by adjusting the design parameters to obtain favourable results. The results were analyzed based on the differential pressure exerted on the disc. These optimum parameters shall indicate that the levitating disc will work effectively and autonomously inside the completion string during production. It will also verify that the design parameters are critical to ensure that the production performance was enhanced.